Search for the production of dark matter in association with top-quark pairs in the single-lepton final state in proton-proton collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2015)
A search is presented for particle dark matter produced in association with a pair of top quarks in pp collisions at a centre-of-mass energy of root s = 8TeV. The data were collected with the CMS detector at the LHC and correspond to an integrated luminosity of 19.7 fb(-1). This search requires the presence of one lepton, multiple jets, and large missing transverse energy. No excess of events is found above the SM expectation, and upper limits are derived on the production cross section. Interpreting the findings in the context of a scalar contact interaction between fermionic dark matter particles and top quarks, lower limits on the interaction scale are set. These limits are also interpreted in terms of the dark matter-nucleon scattering cross sections for the spin-independent scalar operator and they complement direct searches for dark matter particles in the low mass region.
Keywords: Hadron-Hadron Scattering; Beyond Standard Model; PARTON DISTRIBUTIONS